Star trek chronology: the history of the future - Okuda, Dense; Okuda, Michael (New York: Pocket Books, 1996)
Este texto trata sobre las generaciones de Star Trek
Colección Erwin Buendia Silva 2431
Keywords: Cine - Star Trek